Avaliação do óleo da semente de cupuaçu (Theobroma grandiflorum) extraído por banho ultrassônico e pelo método de Soxhlet com diferentes solventes - Bençal, Geslia Thaise (2024)
Cupuaçu (Theobroma grandiflorum) is a native Brazilian fruit, belonging to the Sterculiaceae family, widely consumed in Brazil. It stands out for the characteristic flavor of its acidic pulp and intense aroma. Its seed has its fate neglected, turning into a waste, although it has a large amount of oil in its structure. The extraction of vegetable oils can be done using various organic solvents, such as hexane, but in this case, we sought to replace it with alternative solvents, such as ethanol, isopropanol and ethyl acetate, due to its toxicity, aiming at a better quality of the oils linked to a similar amount. The factors that act on the extraction mechanisms are temperature, particle size and the type of method used. Therefore, extraction was also carried out using two different methods, Soxhlet and ultrasound, with the aim of proving the difference in oil quality due to high temperatures. The present work aims to extract cupuaçu oil by the Soxhlet and ultrasound methods and characterize them by gas chromatography and the DPPH (2,2-diphenyl-1-picrylhydrazyl) method, quantitatively analyzing the presence of antioxidant activity in the samples. Thus, it was possible to correlate the results of the tests according to the solvent used and the extraction method studied. An oil yield of between 10 and 36% was obtained using ultrasound, with 10% obtained with ethanol and 36% with ethyl acetate, and 25 to 36%, with 25% obtained with ethanol and 36% with isopropanol. In relation to gas chromatography data, it was observed that fatty acids did not suffer major variations with the change of method and solvent when analyzing the data obtained by gas chromatography, with the predominance being oleic and stearic acids, as literature. The results for antioxidant activity were high with all solvents and regardless of the protection method, varying between 26%, with ethyl acetate, to 103%, with ethanol. It is concluded that oil extraction with alternative solventes was efficient, given that it obtained good results for fatty acids analysed and high antioxidant potential in the cupuaçu oil.